EMPLOYEE WELL BEING DITINJAU DARI ORGANIZATIONAL JUSTICE DAN JOB DEMAND PADA TENAGA AHLI LABORATORIUM MEDIK (ATLM) - Cahya Milia Tirta Saftri; Laelatul Anisah; Annisa Baitina (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
This research aims to find out the relationship between organizational justice and job demand on employee well-being of medical laboratory experts (ATLM). The subjects in this research were 100 medical laboratory experts (ATLM) with the criteria of having worked for at least 1 year, having an active Registration Certificate (STR), a minimum of 1 year of service and being male or female. The research results show the major hypothesis, namely that there is a significant relationship between organizational justice and job demand on employee well-being with a correlation value of Ry(1,2) of 0.636, calculated F of 25,052 P=0.000 (p < 0.05). Meanwhile, the first minor hypothesis is that there is a significant positive relationship between organizational justice and employee well-being with a correlation value of r1y = 0.481 p = 0.000 (p < 0.05). That is, the higher the organizational justice, the higher the level of employee well being. Furthermore, for the second minor hypothesis, there is a significant negative relationship between job demand and employee well-being with a correlation value r1y = 0.481 p = 0.00 (p < 0.05). This means that the higher the job demand, the lower the level of employee well being among medical laboratory experts.. Keywords: Employee Well Being; Organizational Justice; Job Demand; Medical Laboratory Experts (ATLM)